The Influence of Celebrity Endorser Credibility and Brand Image on Purchase Decisions of Glad2Glow Skincare in Bandar Lampung - Mila Fadila; Aida Sari; Driya Wiryawan (Harmony Management: International Journal of Management Science and Business, 2025)
This research aims to examine the impact of celebrity endorser credibility and brand image on consumers' purchasing decisions regarding Glad2Glow skincare products in Bandar Lampung. The intense competition in the beauty industry pushes companies to adopt innovative marketing strategies, such as leveraging trustworthy celebrity endorsers and building a strong brand image. A quantitative approach was used in this study, with data gathered from 160 Glad2Glow skincare users in Bandar Lampung through questionnaires. The data were analyzed using multiple linear regression. The findings reveal that the credibility of celebrity endorsers has a positive and significant influence on purchasing decisions. Similarly, brand image also exerts a positive and significant impact. Together, these factors play a key role in improving consumers' buying decisions. The results underscore the importance of credible endorsements and a solid brand image in gaining consumer trust and driving the purchase of local skincare products in a highly competitive market.